DIRECT EFFECT ANALYSIS OF ONLINE INTEGRATED BANKING SYSTEM IMPLEMENTATION ON CUSTOMER SATISFACTION AND COMPLIANCE OF SUMUT BANK - Maharaja, Jannes; Lubis, Irsyad (Faculty of Economic and Business, University of Pasundan, 2024)
This study investigates the influence of the OLIBs management information system implementation in PT Bank Sumut Pematang Siantar Branch's banking services on customer satisfaction, loyalty, and compliance. Employing quantitative analysis via Smart PLS, collected data was assessed. Outcomes highlight a significant positive impact of OLIBs on customer satisfaction, loyalty, and compliance. Smart PLS analysis establishes notable connections between OLIBs-related factors (service quality, accessibility, personalization, data security) and customer-oriented aspects. The study suggests that embracing OLIBs can amplify customer satisfaction, loyalty, and compliance. Implications extend to PT Bank Sumut Pematang Siantar Branch and other financial entities, providing insights to refine strategies, uphold robust relationships, and ensure compliance, ultimately enhancing overall customer experiences.